A Comparative Review of Selected Urdu Books on Seerat e Aisha R. A - Dr. Aqsa; Prof. Dr. Muhammad Ijaz (jihat-ul-islam, 2023)
This is a short account of Hazrar Aisha R.A Seerat, meant to shed light on the individual personality according to Islam. It is derived from the Quran (33:6): "The Prophet is closer to the believers than their selves, and his wives are (as) their mothers". The following objective in this article is aimed at research introducing the importance of Hazrat Ayesha’s R.A biography, so that the new generation can plan their lives in the light of Ayesha’s Seerat. In this article, we discussed the biographies of Hazrat Aisha R.A. Furthermore, we selected 12 books that have been written in the form of biographies and then we compared these books based on supremacy and many other characteristics. Allah wanted them to be a living example of faith, piety, knowledge, wisdom, and noble morals and indeed, they truly were. Furthermore, owing to their intimate association with the Prophet’s and his teaching, what they had witnessed of his refined manners, they became examples for all other women in piety and in the commendable treatment of the husband. Allah favored him by glorifying in Qur’an. That is and will always be living in the hearts and the minds of the Muslims.